4 - Youth Masculinities in Zimbabwe’s Congested Gerontocratic Political Space - Jaji, Rose (Africa Development, 2020)
This article situates its discussion of young Zimbabwean men’s performance of masculinity in a restrictive political space in a broader continental context in which the majority of young people are politically and economically marginalised. It addresses how the older generation’s domination and monopolisation of political space presents obstacles to the youth’s aspiration to perform normative masculinity. The article also discusses various strategies the youth in Zimbabwe are devising to claim space in a political arena that can be characterised as a gerontocracy. The youth seek relevance in Zimbabwe’s congested and gerontocratic political space through strategies that range from co-opting gerontocratic masculinities to subverting them. Notwithstanding the divergence in these strategies, young people who adopt them to create and occupy space in Zimbabwe’s political terrain legitimise their choices by appealing to culture, thus showing how culture can be harnessed for contradictory objectives in the performance of masculinities. The strategies also draw from global trends involving the youth’s engagement in non-traditional political participation facilitated by their dominance of virtual, social media space.